State Messaging on Toxic Chemical Exposure: Per- and Polyfluoroalkyl Substances and the Individualization of Risk on State Websites in the United States. Issue 8 (17th November 2021) - Zindel, Helena; Powers, Martha; Brown, Phil; Cordner, Alissa
ABSTRACT : Government websites are an important tool for communicating information about environmental exposures and emerging public health concerns to the public. This includes how US state websites frame risks associated with per- and polyfluoroalkyl substances (PFAS) and how these risks are communicated to the public through e-government. We conducted a content analysis of US states' websites about PFAS, analyzing narratives on federal regulation, health outcomes, the framing of risk, and the role of individual behavior in exposure reduction. We found that 70% (35/50) of states had PFAS-specific websites. On these sites, personal responsibility was emphasized over corporate accountability, and health risks were communicated unevenly across states. Discrepancies in the type and availability of information presented could make it difficult for residents to be adequately and equally informed about PFAS contamination and associated adverse health outcomes.